Baptisms by Fire: Future Wars in Early Canadian Speculative Fiction - Weiss, Allan (Studies in Canadian Literature, 2014)
From 1871 to the First World War, a large number of fictional works portraying future wars were published in Europe and North America. At that time, many thinkers saw war not as a necessary evil but as a nation-building exercise. During that period, Canadian novels and stories appeared that dramatized future military conflicts, mostly but not always with the United States. Texts like W.H.C. Lawrence’s The Storm of ’92 (1889), Ralph Centennius’s “The Dominion in 1983” (1883), and Ulric Barthe’s Similia similibus (1916) exhibit many of the conventions of British and American future-war fiction, with some noteworthy differences produced by Canada’s position in the world. Given its status as a colony and relative lack of strength, Canada is portrayed not as a major player in world affairs but rather as the victim of the geopolitical machinations of other, more powerful countries. Analyzing these texts also reveals that early Canadian speculative fiction shared a more general literary purpose that critics have detected in much of the country’s fiction, drama, and poetry of the period: not just the articulation but even the creation of a national identity.